2014
DOI: 10.1371/journal.pone.0102758
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin Neurotoxicity Involves Peroxisome Alterations. PPARγ Agonism as Preventive Pharmacological Approach

Abstract: The development of neuropathic syndromes is an important, dose limiting side effect of anticancer agents like platinum derivates, taxanes and vinca alkaloids. The causes of neurotoxicity are still unclear but the impairment of the oxidative equilibrium is strictly related to pain. Two intracellular organelles, mitochondria and peroxisomes cooperate to the maintaining of the redox cellular state. Whereas a relationship between chemotherapy-dependent mitochondrial alteration and neuropathy has been established, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 70 publications
2
55
0
3
Order By: Relevance
“…In our research, we have already characterized ROS as central players of oxaliplatin CIN using in vitro and in vivo models [4,20,35]. The results herein presented show that the SOD mimetic poliaminopolicarboxylic compound MnL4 prevents cellular damage induced by oxaliplatin in vitro, reducing oxidative stress and normalizing calcium dynamic in isolated astrocytes pre-treated with the anticancer drug.…”
Section: Discussionmentioning
confidence: 79%
“…In our research, we have already characterized ROS as central players of oxaliplatin CIN using in vitro and in vivo models [4,20,35]. The results herein presented show that the SOD mimetic poliaminopolicarboxylic compound MnL4 prevents cellular damage induced by oxaliplatin in vitro, reducing oxidative stress and normalizing calcium dynamic in isolated astrocytes pre-treated with the anticancer drug.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, catalase induction by PPARγ may be independent of the process of peroxisome proliferation in individual cell types. Zanardelli and colleagues reported that astrocytes respond with an increase in peroxisome proliferation induced by the PPARγ antagonist G3335 but in parallel decreased catalase expression, whereas rosiglitazone as a PPARγ agonist, did not increase peroxisome abundance but induced catalase expression [191]. This implies that the peroxisome proliferation reported after G3335 administration is a compensatory response to antagonize the specific reduction in catalase levels caused by the inhibition of PPARγ.…”
Section: Other Ppar Family Membersmentioning
confidence: 99%
“…oxaliplatin dosing and clinically relevant levels of oxaliplatin (as inorganic platinum) in plasma (Zanardelli et al. 2014). …”
Section: Limitationsmentioning
confidence: 99%